I CONGRESS OF THE CHILDREN'S URINOLOGISTS AND ANDROLOGISTS - S.N. Zorkin (Union of pediatricians of Russia, 2009)
The Ist Congress of specialists in pediatric urology and andrology was orginised by Interregional public organization of pediatric urology and andrology (IPOPUA) and held in Moscow December 12-13, 2008.